Declining Food Security in a Philippine Oil Palm Frontier: The Changing Role of Cooperatives. Issue 5 (5th August 2018) - Montefrio, Marvin Joseph F.; Dressler, Wolfram H.
ABSTRACT: The long‐held redistributive function of agricultural cooperatives — one of moral economy and poverty alleviation — has changed dramatically as they emerge as core brokers for agro‐industrial development in the so‐called 'green economy'. This article examines the changing role of cooperatives involved in brokering oil palm production and its impact upon the food security and livelihoods of smallholders who labour in plantation regimes situated in historically uneven agrarian political economies. Findings show how, increasingly, cooperatives reinforce uneven agrarian social relations of production and exchange in which indigenous smallholders experience loss of land, poor wage labour conditions tinged with insecurity and prejudice, and mounting debt in an expanding oil palm complex. The article suggests that these changes in agrarian social relations negatively influence indigenous farmers' food security pathways, with their access to and use of appropriate foods diminishing. It asserts that understanding the impacts of cooperatives on food security pathways requires a relational and situated analysis of livelihood change and agrarian relations in extractive frontiers.